Unraveling the phenological diversity of corn effects on environmental stress in Wisconsin - Lin, Jueyu; Zhang, Deshuai; Ding, Ying; Zhu, Peng; Sun, Ying (Proceedings of SPIE, the international society for optical engineering, 2024)
Under the influence of climate change, it is crucial for humanity to address the challenges to agricultural production, particularly the disruptions in the supply of agricultural products. This study focuses on the state of Wisconsin and uses corn as the subject of research. We utilize the Near-Infrared Reflectance of vegetation (NIRv) index derived from the time series of Sentinel-2 and Landsat 8 images from 2017 to 2023 to assess the phenological diversity of corn. Additionally, we evaluate the stability of crop yield as an indicator of the agroecosystem's resilience to the impacts of climate change. The influence of corn phenological diversity on yield stability is quantified using the Random Forest Regression model. The results indicate that higher crop phenological diversity can mitigate the climatic stresses encountered during the crop growth process.